DEVELOPMENT OF DESIGNS AND JUSTIFICATION OF THE PARAMETERS OF A SCRETTING DRUM WITH A DAMPER OF A SPINNING MACHINE - Juraev Anvar Juraevich; Urakov Nuriddin Abramatovich (Galaxy International Interdisciplinary Research Journal, 2022)
The article provides an analysis of the features of existing designs of the discretizing drum of a spinning machine. The structural scheme and the principle of operation of the recommended composite discretizing drum with a shock absorber and sectional gear sets are presented. The results of theoretical studies of vertical vibrations of sectional toothed sets of a discretizing drum. On the basis of the obtained patterns of vibrations of gear sets and the constructed graphic dependencies, the main parameters of the drum are substantiated.